Platysma Flap for Mandibular Reconstruction: A Case Report - Mukul, Sailesh Kumar; Rashid, Sibgutulah; Mishra, Rajni; Gupta, Vyakhya Akhileshkumar (Journal of Orofacial Research, 2025)
The platysma myocutaneous flap (PMF) is a versatile option for reconstructing small to medium sized defects in the oral cavity due to its thin, pliable nature and reliable vascularity. This case report illustrates the successful application of a PMF for mandibular reconstruction following marginal mandibulectomy in a 58 year old patient with acanthomatous ameloblastoma. The flap provided adequate soft tissue coverage with minimal donor site morbidity. While the initial recovery was uneventful, a late complication of screw loosening in the reconstruction plate was managed effectively. At 1 year follow up, the surgical site demonstrated successful healing with a viable flap and no functional impairment. This case highlights the PMF's utility in oral reconstruction, emphasizing its simplicity and reliability when applied with meticulous surgical technique and vigilant postoperative monitoring.